Towards an engineered autologous cellular therapy for RAG2 deficiency - Gardner, CL (2020)
Severe combined immune deficiency (SCID) caused by RAG deficiency is a genetically-determined immune deficiency characterized by the virtual absence of adaptive immune cells. Unless treated with a hematopoietic stem cell transplantation (HSCT), RAG deficient patients succumb to severe infections early in life. HSCT, however, carries risks of graft-versus-host disease. Moreover, a high rate of graft failure and poor immune reconstitution have been reported after unconditioned HSCT. Expression of the RAG genes is tightly regulated, and preclinical attempts of gene therapy with heterologous promoters have led to controversial results. Using patient-derived induced pluripotent stem cells (iPSCs), patient hematopoietic stem and progenitor cells (HSPCs) and an in vitro artificial thymic organoid system as a model, here we demonstrate that gene editing rescues the progressive T-cell differentiation potential of RAG2 deficient cells to normal levels, with generation of a diversified T cell repertoire. These results suggest that gene editing may represent a novel autologous therapeutic option for correction of this immunodeficiency.